2008
DOI: 10.1002/cjce.5450830324
|View full text |Cite
|
Sign up to set email alerts
|

The Parastillation Efficiency and Hydrodynamic Behaviour

Abstract: This paper investigates some aspects of the parastillation process, which employs a unique distillation column. A laboratory scale apparatus was used to study the parastillation column. Experiments were carried out under total and partial reflux conditions, using an ethanol‐water system. Experiments were conducted to analyze the influence of the vapour flow rate and reboiler initial ethanol concentration on the hydrodynamic conditions. Limiting operating conditions were defined. Murphree separation efficiencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 2 publications
0
8
0
2
Order By: Relevance
“…The construction of laboratory-scale parastillation columns for ethanol-water distillation was reported by Belincanta et al, , de Moraes, and Di Domenico . Belincanta et al , did not have operational problems related to the division of phases, in parastillation columns with 12 stages.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The construction of laboratory-scale parastillation columns for ethanol-water distillation was reported by Belincanta et al, , de Moraes, and Di Domenico . Belincanta et al , did not have operational problems related to the division of phases, in parastillation columns with 12 stages.…”
Section: Introductionmentioning
confidence: 99%
“…The construction of laboratory-scale parastillation columns for ethanol-water distillation was reported by Belincanta et al, , de Moraes, and Di Domenico . Belincanta et al , did not have operational problems related to the division of phases, in parastillation columns with 12 stages. The authors reported that in the parastillation column, a foam (cellular and homogeneous) regime occurred more often than expected for a conventional column.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In metastillation, the division is in the liquid phase. Prior works demonstrate, by increasing the number of phase divisions, the possibility to reduce the energy consumption and equipment cost, with respect to conventional distillation. The division of the liquid phase permits to reduce the stage area of metastillation columns up to 30% in relation to conventional distillation . Additionally, metastillation columns may present higher Murphree efficiencies than conventional columns .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there are no works considering the phase split ratio as a process variable that can be manipulated and controlled. Few computational simulation works have considered phase division always into two equal parts, ,,, while experimental works did not strictly control the phase split ratio. , Molar differences in the internal flows of the columns may affect the separation process. Variations of only 6%, in the vapor flow of one parastillation side in comparison to the other side, caused a variation of almost three times in the Murphree efficiency values in the alcoholic distillation investigated in lab equipment .…”
Section: Introductionmentioning
confidence: 99%